2010
DOI: 10.1073/pnas.1013758107
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative assessment of meningococcal antigens to evaluate the potential strain coverage of protein-based vaccines

Abstract: A unique multicomponent vaccine against serogroup B meningococci incorporates the novel genome-derived proteins fHbp, NHBA, and NadA that may vary in sequence and level of expression. Measuring the effectiveness of such vaccines, using the accepted correlate of protection against invasive meningococcal disease, could require performing the serum bactericidal assay (SBA) against many diverse strains for each geographic region. This approach is impractical, especially for infants, where serum volumes are very li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
295
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(309 citation statements)
references
References 30 publications
5
295
0
2
Order By: Relevance
“…30 While 4CMenB coverage of non-serogroup B strains has not been studied extensively, the susceptibility of any meningococcal strain to bactericidal antibodies elicited by 4CMenB is dependent upon both the degree of similarity between vaccine antigens and the respective target proteins, as well as the expression level of the target proteins, in each strain. 31 In the current study, following 2 doses of the rMenB vaccine alone, we observed bactericidal antibody responses against the serogroup A test strain, in particular, and to a lesser extent the serogroup C and W test strains. Given the robust immune responses against serogroups ACWY following vaccination with MenACWY-CRM, the potential additive cross-protective benefit against these serogroups, as well as against serogroup X, conferred by combining MenACWY-CRM with the rMenB and OMV components deserves further clinical evaluation.…”
Section: Discussionmentioning
confidence: 79%
“…30 While 4CMenB coverage of non-serogroup B strains has not been studied extensively, the susceptibility of any meningococcal strain to bactericidal antibodies elicited by 4CMenB is dependent upon both the degree of similarity between vaccine antigens and the respective target proteins, as well as the expression level of the target proteins, in each strain. 31 In the current study, following 2 doses of the rMenB vaccine alone, we observed bactericidal antibody responses against the serogroup A test strain, in particular, and to a lesser extent the serogroup C and W test strains. Given the robust immune responses against serogroups ACWY following vaccination with MenACWY-CRM, the potential additive cross-protective benefit against these serogroups, as well as against serogroup X, conferred by combining MenACWY-CRM with the rMenB and OMV components deserves further clinical evaluation.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, we further addressed functionality and breadth of antibodies by performing bactericidal killing assays using three different N. meningitidis strains (MC58, M4407, and NZ98/254). The serum bactericidal titers (SBAs) for each MenB strain depend not only on the immunogenicity of the vaccine but also on the level of expression and on the sequence similarity of the three vaccine antigens used (23). Vaccination with the plain vaccine induced high SBA titers for strain MC58, expressing high levels of a conserved fHBP antigen in WT mice; however, this response was reduced by four times in Nlrp3-deficient mice (Fig.…”
Section: Nlrp3-deficient Mice Respond Well To Rmenb Vaccine When Adjumentioning
confidence: 99%
“…Immunity toward infection with N. meningitidis correlates with the presence of bactericidal antibodies, which kill the bacterium in the presence of complement (23). Therefore, we further addressed functionality and breadth of antibodies by performing bactericidal killing assays using three different N. meningitidis strains (MC58, M4407, and NZ98/254).…”
Section: Nlrp3-deficient Mice Respond Well To Rmenb Vaccine When Adjumentioning
confidence: 99%
“…By using multiple antigens 4CMenB offers broad protection, which can only be assessed using techniques such as the meningococcal antigen typing system (MATS) that employs a sandwich ELISA to predict the likelihood that individual strains will be killed in the hSBA. 13,14 Applying MATS to over 1000 strains isolated across eight European countries predicted that the current 4CMenB formulation would cover 78% (95% CI 63-90) of all strains, and that over half of the strains would be targeted by more than one antigen. 15 This is probably a conservative estimate as the MATS technique does not allow any estimate of synergies due to different antigens, nor does it take into account potential immune responses for minor components such as additional nonPorA proteins in the OMV.…”
Section: Discussionmentioning
confidence: 99%